The social capital in business organizations: A case study of PT Asia Motor vehicle insurance claim polysindo crime in Jakarta - Anton Lie, Antonius (International Journal for Educational and Vocational Studies, 2022)
In recent years, general insurance companies have received attention from the public due to their denial of trust, the weakness of human capital, and physical capital goods. This denial has reduced the energy of social capital which has implications for the low productivity of companies, especially insurance companies. An insurance company at least involves a number of interrelated and cooperating parties, namely: 1) the company, 2) the customer and 3). partner party. The aims of this research are: a. to study and describe the role of social capital in a business organization, especially for the insurance business in Indonesia. b. explain aspects of social capital in PT. Asia Krimere Polysindo (Headquarters and Central Department of Car Insurance Claims) between 1992 and 2005, in relation to the claims process involving external networks such as customers, corporate partners (banks, leasing companies, insurance agents, brokers, workshops) and with other insurance companies. c. identify synergies between financial capital, human capital, physical capital goods and social capital in the organizational structure of the insurance business. From the results of research on synergy between capitals, researchers found 4 patterns of synergy resulting from synergies between human capital, financial capital, physical capital goods and social capital in increasing the productivity of a business organization, namely: 1. Weak positive synergy pattern, 2. Weak synergy pattern negative, 3. Negative strong synergy pattern, 4. Positive strong synergy pattern. corporate partners (banks, leasing companies, insurance agents, brokers, repair shops) and with other insurance companies. c. identify synergies between financial capital, human capital, physical capital goods and social capital in the organizational structure of the insurance business. From the results of research on synergy between capitals, researchers found 4 patterns of synergy resulting from synergies between human capital, financial capital, physical capital goods and social capital in increasing the productivity of a business organization, namely: 1. Weak positive synergy pattern, 2. Weak synergy pattern negative, 3. Negative strong synergy pattern, 4. Positive strong synergy pattern.